Modeling of continuous self‐classifying spiral jet mills part 2: Powder‐dependent parameters from characterization experiments. Issue 12 (18th October 2014) - Starkey, Derek; Taylor, Cathy; Siddabathuni, Sunil; Parikh, Jinit; Svoronos, Spyros; Mecholsky, John; Powers, Kevin; Iacocca, Ron
<x xml:space="preserve">Abstract</x> The milling model described in Part 1 has been expanded to a three‐level model with the addition of powder‐dependent parameter function models with simple material characterization measurements as inputs. This allows the determination of these parameters with minimal consumption of powder. Specifically, the powder‐dependent parameters are related to material hardness from microindentation or to a breakage measure from single‐impact milling. Three crystalline powders, sodium bicarbonate, lactose monohydrate, and sucrose, have been used to test the described material characterization techniques and expanded milling model. © 2014 American Institute of Chemical Engineers AIChE J 60: 4096–4103, 2014